Hypertrophic olivary degeneration: A case report - Özdemir, Meltem; Turan, Aynur; Kavak, Rasime Pelin; Dilli, Alper (Indian Journal of Radiology and Imaging, 2019)
Hypertrophic olivary degeneration is a rare occurrence in which different pathological processes including enlargement and vacuolation of the neurons, demyelination of the white matter, and fibrillary gliosis of the inferior olivary nucleus take place. It mostly develops secondary to a destructive lesion involving the Guillain–Mollaret pathway. The mostly reported destructive lesions causing hypertrophic olivary degeneration are stroke, trauma, tumors, neurosurgical interventions, and gamma knife treatment of brainstem cavernoma. It presents with symptomatic palatal tremor, and typically appears as an expansive nonenhancing nodular lesion that shows increased signal intensity on magnetic resonance imaging (MRI). The identification of hypertrophic olivary degeneration on MRI is of great importance as its MRI appearance is very similar to those of more severe pathologies, including tumors, infarction, demyelinating lesions, and infections. We present a case of hypertrophic olivary degeneration in a patient with a history of ischemic stroke two years before the development of palatal tremor.
Keywords: Guillain–Mollaret triangle; hypertrophic olivary degeneration; magnetic resonance imaging